A climate database with varying drought-heat signatures for climate impact modelling ... - Tschumi, Elisabeth; Lienert, Sebastian; van der Wiel, Karin; Joos, Fortunat; Zscheischler, Jakob (Zenodo, 2020)
To allow for impact modelling for a wide range of sectors, we provide six scenarios with differing drought-heat signatures. Each scenario is 100 years long and we provide temperature variables (mean, minimum, maximum), precipitation, radiation (short- and longwave downward radiation and shortwave net radiation) and wind (zonal and meridional) at daily timescales. All variables are available at a regular 1◦×1◦grid over land, except Antarctica and large parts of Greenland. Leap days were removed, so there are 365×100 time steps for each scenario. ... : E.T. and J.Z. acknowledge the Swiss National Science Foundation (Ambizione grant 179876). K.v.d.W. acknowledges funding for the HiWAVES3 project from the National Natural Science Foundation of China (41661144006) ...